Profile Students Critical Thinking Skill on Reproductive System Materials - Dewi Hayatu Nupus; Ading Pramadi; Asrianty Mas'ud (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
This study aims to analyze and determine students' critical thinking skills on the material of the reproductive system. The method of this research is descriptive quantitative. The sample of this research is 98 students. The data is an analyzed test question. Instruments use critical thinking skills, according to Ennis. Data analysis technique using descriptive analysis. The data analysis results showed that students' critical thinking skills were the highest category (72.12%). The dominant is based on the data analysis, a high category in making strategies and tactics (82.36%) and providing further explanations (79.34%). Providing an elementary clarification of 66.42% and inference Â 71.05% is enough. The lowest was found in basic support skills (60.03%). Overall, studentsâ€™ CTS was high. But that is needed to be improved. Therefore, the teachers must provide test questions with more varied learning models.